2022
DOI: 10.1088/1755-1315/999/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Safe Construction And Visual Pollution Of Billboards Along Main Street

Abstract: The installation of billboard building construction, especially along main urban roads, is not the same as building construction such as residential buildings, warehouses and others. There are several things that need to be considered both from the aspect of construction safety and environmental appearance, so it is necessary to assess the condition of the billboard installed. The failure to build billboards can cause collapse. This happens because planning activities are not carried out according to technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…The implemented customized CNN model attained a training accuracy of 95% and a validation accuracy of 85%. Andjarsari and her team [16] reported that the presence of billboards and street graffiti along the route could impact the area's aesthetics and potentially obstruct vision. To investigate visual pollution, the authors employed an AHP-based SBE technique.…”
Section: Related Workmentioning
confidence: 99%
“…The implemented customized CNN model attained a training accuracy of 95% and a validation accuracy of 85%. Andjarsari and her team [16] reported that the presence of billboards and street graffiti along the route could impact the area's aesthetics and potentially obstruct vision. To investigate visual pollution, the authors employed an AHP-based SBE technique.…”
Section: Related Workmentioning
confidence: 99%